Dual Functions in Response to Heat Stress and Spermatogenesis: Characterization of Expression Profile of Small Heat Shock Proteins 9 and 10 in Goat Testis. (22nd January 2015) - Xun, Wenjuan; Shi, Liguang; Cao, Ting; Zhao, Chunping; Yu, Ping; Wang, Dingfa; Hou, Guanyu; Zhou, Hanlin
Abstract : Small heat shock proteins 9 and 10 (HSPB9 and HSPB10) are two testis-specific expressed sHsps. The objective of this study was to investigate the mRNA expression profile of HSPB9 and HSPB10 in goat testis among the different seasons, ages, and environmental temperatures. Allocation of the two sHsps was also performed by immunohistochemistry. The results showed that the transcript levels of HSPB9 and HSPB10 were extremely high in the testis ( P < 0.01 ) . The relative expression of HSBP9 and HSPB10 in testis showed a tendency to increase with age and then is maintained at the constant level after sexual maturity. HSPB9 and HSPB10 have significantly higher expression in the breeding season ( P < 0.05 ) and hot season ( P < 0.01 ) . Both HSPB9 and HSPB10 were found to be upregulated by high-temperature stress in testis ( P < 0.05 ), and the expressions of Hsp70 and Hsp90 were also increased simultaneously ( P < 0.01 ) . Immunohistochemistry analysis localized HSPB9 expressed in spermatogonia, spermatocytes, and round spermatids and HSPB10 expressed in the elongate spermatids. In epididymis, strongly staining signal of HSPB10 was detected in pseudostratified columnar epithelium. In conclusion, the two testis-specific sHsps are closely related to male reproduction and heat tolerance. The results could provide valuable data for the further studies on HSPB9 and HSPB10.